“I have taken your izzath (honour), so you can’t betray me”: Young people’s lived experiences of navigating sexual norms and violence in Bangladesh - Prima Alam; Ana Bolio; Nandan Thakkar; Cicely Marston (Cogent Public Health, 2023)
AbstractLimited sexual health communication between young people and adults combined with widespread gender discrimination restrict young people’s access to reliable information and services in Bangladesh. Although taboos around sexuality have been documented in health research, there is little in-depth research on how young people navigate socio-sexual norms in their everyday lives. The objective of this article is to identify and discuss perceived socio-sexual norms and how young people experience and navigate these. This article is based on ethnographic data generated in Dhaka, Bangladesh in 2019 as part of the first author’s doctoral research. Using thematic analysis, we draw on experiences of sexual norms and violence from in-depth biographical interviews with 46 individuals aged 18 to 24 from middle- or working-class backgrounds. Young people identified sexual abstinence before marriage as a key norm and highlighted several challenges when trying to negotiate this norm in practice. Widespread perception that penetrative sex “bonds” a person to one sexual partner for life contributes to coercive behaviour. Experiences of, and silence around, sexual abuse and harassment affects young people’s confidence in subsequent sexual interactions. Young people described lives punctuated by violence that helped ensure a lack of justice for survivors. Limited sexual health communication between young people and adults combined with widespread gender discrimination restrict young people’s access to reliable information and services in Bangladesh. Although taboos around sexuality have been documented in health research, there is little in-depth research on how young people navigate socio-sexual norms in their everyday lives. The objective of this article is to identify and discuss perceived socio-sexual norms and how young people experience and navigate these. This article is based on ethnographic data generated in Dhaka, Bangladesh in 2019 as part of the first author’s doctoral research. Using thematic analysis, we draw on experiences of sexual norms and violence from in-depth biographical interviews with 46 individuals aged 18 to 24 from middle- or working-class backgrounds. Young people identified sexual abstinence before marriage as a key norm and highlighted several challenges when trying to negotiate this norm in practice. Widespread perception that penetrative sex “bonds” a person to one sexual partner for life contributes to coercive behaviour. Experiences of, and silence around, sexual abuse and harassment affects young people’s confidence in subsequent sexual interactions. Young people described lives punctuated by violence that helped ensure a lack of justice for survivors.